Screening for social anxiety disorder in students of Jordan universities after COVID-19 pandemic: a cross-sectional survey study - Abdallah Y Naser; Othman Beni Yonis; Ahlam J Alhemedi; Hadeel Allan; Ghalia abu Mohsen; Ayham Almasri; Haitham Abdulrazzeq; Islam Khasawneh; Osama El-khateeb (BMJ Open)
Objective To examine the prevalence rate of social anxiety disorder (SAD) among university students in Jordan after the COVID-19 pandemic and its associated predictors.Design A cross-sectional online survey study that was conducted in Jordan between January and December 2023.Setting: Universities in Jordan.Participants Healthy university students from any specialty currently enrolled at a Jordanian university.Primary outcome measure The prevalence rate of SAD, which was assessed using the Social Phobia Inventory.Results A total of 851 university students participated in this study. More than half of them (65%) were women. The mean age of the study participants was 21.9 (2.7) years. The majority of them (70.6%) were studying medical fields. The median number of times the study participants got infected with COVID-19 was 1.0 (IQR: 0.0–2.0). The median number of viewing hours spent on social networking sites was 4.0 (IQR: 3.0–6.0). The median SAD score was 19 (IQR: 10–32) out of 68, which represents 27.9% of the maximum attainable score. Up to 45.4% of the study participants were susceptible to SAD, with 12.5% of the study participants reporting severe to very severe SAD symptoms. Students older than 21.9 years were 32% less likely to report SAD symptoms compared with younger students (p<0.01).Conclusion Jordanian universities students are increasingly likely to report SAD symptoms. The data show how important it is for universities to recognise and deal with this mental health issue. Focused treatments and support networks could help students with social anxiety problems to deal with them.